GAMBARAN PENGETAHUAN, PRAKTEK MENYUSUI DAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SAIGON - Istiqomah; Martinus Ginting; Didik Hariyadi; Iman Jaladri; Yanuarti Petrika; Nurrizky Natasha Gunawan (Jurusan Gizi Poltekkes Pontianak, 2024)
Breast milk is the best food and drink for babies because breast milk contains nutrients. Exclusive breast milk is breast milk that is given to babies from birth for six months, without adding or replacing it with other foods or drinks except medicines, vitamins and minerals. Nationally, the target for exclusive breastfeeding in Indonesia is 80%, while the coverage of achieving exclusive breastfeeding in Indonesia has only reached 48.6%. Based on data from the Pontianak City Health Service, exclusive breastfeeding coverage at the East Pontianak District Health Center (Saigon) is 39.2%. The aim of this research is to determine the description of knowledge, breastfeeding practices and exclusive breastfeeding in the Saigon Community Health Center working area. This research method. Data analysis used in this research uses univariate analysis using distribution frequencies and uses bivariate analysis using crosstabs. The results of this study found that in the exclusive breastfeeding category (61.9%). Good category knowledge (54.8%). Attachment in this study was categorized as good (57.1%). The breastfeeding position was in the good category (81.0%). How to suck in good category (61.9%). The conclusion is that it is known that knowledge, breastfeeding practices and exclusive breastfeeding are mostly good enough in the Saigon Health Center Working Area.